2001
DOI: 10.1016/s0092-8674(01)00546-3
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Structure of the Large Ribosomal Subunit from a Mesophilic Eubacterium

Abstract: We describe the high resolution structure of the large ribosomal subunit from Deinococcus radiodurans (D50S), a gram-positive mesophile suitable for binding of antibiotics and functionally relevant ligands. The over-all structure of D50S is similar to that from the archae bacterium Haloarcula marismortui (H50S); however, a detailed comparison revealed significant differences, for example, in the orientation of nucleotides in peptidyl transferase center and in the structures of many ribosomal proteins. Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
898
0
25

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 862 publications
(955 citation statements)
references
References 59 publications
32
898
0
25
Order By: Relevance
“…If m > 2, for each (p, q) pair, we find all possible third nucleotides r for which two additional constraints are met: (14) This results in a list of (p, q, r) triples from the RNA 3D structure file which satisfy all pairwise constraints for query motif nucleotides (1, 2, 3). Now we reject some of these partial candidates by applying the subset screening criterion (10) with I = {1, 2, 3}; we reject (p, q, r) triples for which (15) because we can be certain that any m-nucleotide candidate for which (p, q, r) correspond to ( (p 1 ,…, p k , q) for (1, 2,…, k, k + 1) provided that (16) so that all pairwise constraints between the k existing nucleotides and the one new nucleotide are met. We then use the subset screening criterion; we reject those candidates for which: (17) Here S * is the corresponding sum for (p 1 ,…, p k ).…”
Section: Building Lists Of Partial Candidates and The Screening Algormentioning
confidence: 99%
See 1 more Smart Citation
“…If m > 2, for each (p, q) pair, we find all possible third nucleotides r for which two additional constraints are met: (14) This results in a list of (p, q, r) triples from the RNA 3D structure file which satisfy all pairwise constraints for query motif nucleotides (1, 2, 3). Now we reject some of these partial candidates by applying the subset screening criterion (10) with I = {1, 2, 3}; we reject (p, q, r) triples for which (15) because we can be certain that any m-nucleotide candidate for which (p, q, r) correspond to ( (p 1 ,…, p k , q) for (1, 2,…, k, k + 1) provided that (16) so that all pairwise constraints between the k existing nucleotides and the one new nucleotide are met. We then use the subset screening criterion; we reject those candidates for which: (17) Here S * is the corresponding sum for (p 1 ,…, p k ).…”
Section: Building Lists Of Partial Candidates and The Screening Algormentioning
confidence: 99%
“…The database of atomic-resolution RNA 3D structures is growing rapidly [6,7,11,21] and now includes ribozymes [1,14,25], ribosomal subunits [3,16,44] and intact 70S ribosomes [42]. The number, size, and complexity of these structures make manual analyses to find and classify recurrent RNA 3D motifs difficult and time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Studies into the composition and structure of prokaryotic ribosomes have been long-time undertakings and have culminated recently with high-resolution structures for bacterial (Schluenzen et al, 2000;Wimberly et al, 2000;Harms et al, 2001) and archeal (Ban et al, 2000) ribosomal subunits.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of RNA structure have revealed very few long-distance base-pair interactions beyond 800 nt. For example, in the 16S and 23S rRNA structures solved by X-ray crystallography, 99.9% of the pairings are of bases within 600 nt of each other in the primary sequence (Harms, Schluenzen et al 2001;Schuwirth, Borovinskaya et al 2005). Thus, the results from analysis of the accessibility of the Bcl2 coding region should reflect its accessibility in the full length Bcl2 mRNA given that the same structure is predicted of the coding region whether alone or in context of the 5' and 3' UTRs.…”
Section: Discussionmentioning
confidence: 99%